Adapting to environmental challenges : new research in strategy and international business - Torp, Simon; Andersen, Torben Juul (Emerald Publishing Limited, 2020)
The global business environment is as turbulent as ever and organizations must adapt to the changing conditions to survive and persevere. Adapting To Environmental Challenges: New Research In Strategy And International Business provides new promising insights on the effects of middle management involvement in adaptive strategy-making processes and applications of interactive control systems in the pursuit of more durable corporate outcomes. The empirical evidence suggests that responsible corporate behaviour drives higher market-valuations of firms and the application of green technologies is associated with more sustainable performance outcomes. For international organizations that operate across a multiplicity of cultural contexts, the ability to manage responsible corporate behavior must be interpreted in the local contexts and not only in a headquarter context, which is the norm. Hence, multinational managers must appreciate and understand the cultural differences to disentangle the managerial challenges in dynamic global markets where resource-poor firms can forge their international market positions by offering advantageous value-to-price trade-offs induced by supportive cultural values. Adapting To Environmental Challenges: New Research In Strategy And International Business provide new relevant perspectives and insights to understand strategic adaptation in international business contexts based on corporate responsible behavior and cultural sensitivity as the ingredients for agile operations and a resilient multinational organization.
Includes index.
Keywords: Industrial management.; Industrial management -- Decision making.; Sustainable development.; Social responsibility of business.; Business & Economics -- Management.; Business strategy.; elektronické knihy; electronic books